2021
DOI: 10.3390/ijerph18073515
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on High School Student-Athlete Experiences with Physical Activity, Mental Health, and Social Connection

Abstract: COVID-19 restrictions led to reduced levels of physical activity, increased screen usage, and declines in mental health in youth; however, in-depth understandings of the experiences of high school student-athletes have yet to be explored. To describe the experiences of the COVID-19 pandemic on student-athletes’ physical activity, social connection, and mental health, 20 high school student-athletes living in Calgary, Alberta participated in semi-structured interviews, designed using phenomenography. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(115 citation statements)
references
References 44 publications
6
108
0
1
Order By: Relevance
“…These results are also consistent with emerging literature on the role of physical activity in mental health in the context of the COVID-19 pandemic. A study found that implementing fitness programs among adolescents during COVID-19 lockdowns in Italy increased Regulatory Emotional Self-Efficacy scores after 8 weeks [45], and a qualitative study highlighted the role of physical activities and social connections in student-athletes' mental health [46]. However, schools around the world continue to face many challenges to promote physical activities and physical education in the context of COVID-19 [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are also consistent with emerging literature on the role of physical activity in mental health in the context of the COVID-19 pandemic. A study found that implementing fitness programs among adolescents during COVID-19 lockdowns in Italy increased Regulatory Emotional Self-Efficacy scores after 8 weeks [45], and a qualitative study highlighted the role of physical activities and social connections in student-athletes' mental health [46]. However, schools around the world continue to face many challenges to promote physical activities and physical education in the context of COVID-19 [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, schools around the world continue to face many challenges to promote physical activities and physical education in the context of COVID-19 [47,48]. Furthermore, inequalities in resources and built environment can act as barriers to students from lower socio-economic levels, which is something that has to be taken into consideration by educators while planning interventions aiming to increase physical activities [46]. Participation in sports also addressed concerns of limited socializing and communication presented by parents and teachers in the qualitative study in Indonesia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial lockdown restrictions were implemented, the number of studies related to PA and SB during the COVID-19 pandemic has been growing. Previous literature on PA or SB and the present pandemic has mainly focused on the general population [25][26][27][28][29][30][31][32], the older population [33][34][35], people with different chronic illnesses [36][37][38], health care professionals [39] or athletes [40,41]. Employees, and especially office workers, are underrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, exercise and sports activities play a preventive role against mental health exacerbations, so it is extremely important to exercise and participate in sports even during a state of emergency [ 11 ]. As part of the declaration of the state of emergency due to the effects of COVID-19, “stay at home” may also affect those who habitually exercise and play sports [ 12 ]. Due to the declaration of a state of emergency, it was impossible to play sports using the facilities, and except for jogging, most people were forced to limit themselves to exercising at home [ 13 ].…”
Section: Introductionmentioning
confidence: 99%